(untitled) (PerCursos, 2025)
This article seeks to reflect the proposals of Agroecology and Ecodevelopment as a counterpoint to the current development model, especially in brazilian agriculture, which heavily uses the principles of agricultural modernization. The current agricultural model has been causing a trail of environmental and social damage, in a movement that Machado and Machado Filho (2014) describe as “Denial of Nature”. However, new alternatives are beginning to be discussed to reverse (if possible) several of the impacts already present and find new means of development, in a movement treated here in this article as an “Affirmation of Nature”. Agroecology has been gaining space and recognition when discussing agriculture that respects and promotes nature, as well as Ecodevelopment, an alternative proposal, based on local development, balance and environmental care and the endogenous forces of localities.